Delineation of the functional capacity of human neonatal lymphocytes. - Splawski, J B (1991)
Neonatal T cell-B cell collaboration was investigated utilizing a system of T cell-dependent polyclonal B cell activation and Ig secretion. In this system, T cells activated by immobilized anti-CD3 provide a potent stimulus for Ig production by adult lymphocytes. By contrast, anti-CD3 stimulation of cord blood lymphocytes generated minimal numbers of Ig-secreting cells. Ig production by neonatal lymphocytes was enhanced by the addition of Staphylococcus aureus or secreted factors from mitogen-stimulated adult T cells. Supplementation with IL-2 resulted in the production of large amounts of IgM and small amounts of IgG and IgA, with less Ig produced than by comparable cultures of adult lymphocytes. Neonatal T cells proliferated and produced IL-2 in response to immobilized anti-CD3, and supported B cell proliferation and Ig secretion by adult B cells, although not as effectively as adult T cells. Supernatants from activated neonatal T cells were markedly limited in their capacity to support Ig production by adult B cells. Neonatal B cells could be induced to differentiate in response to anti-CD3-stimulated adult T cells. However, the amounts of IgG and IgA secreted were small compared to adult levels. These studies indicate a relative, but not absolute, functional deficiency of both neonatal B and T cells.